Literature Review on Fem Analysis Of Disc Brake System (International Journal of Engineering and Computer Science, 2015)
This paper reviews numerical methods and analysis procedures used in the study of automotive disc brake. It coversFinite element Method approaches in the automotive industry, the complex Contact analysis. The advantages andlimitations of each approach will examine. This review can help analysts to choose right methods and make decisionson new areas of method development. It points out some outstanding issues in modeling and analysis of disc brakesqueal and proposes new conceptual design of the disk braking system. It is found that the complex Contact analysis isstill the approach favored by the automotive industry